Bond Strength of Reinforced Autopolymerized Acrylic Resin to Denture Base Resin - Napapa Aimjirakul; Chavinee Apimanchindakul; Basel Mahardawi; Pheeradej Na Nan; Suwit Wimonchit; Natthamet Wongsirichat (International Journal of Biomaterials, 2023)
The aim of this study was to analyze the effect of applying short E-glass fiber (SEG) and ultrahigh molecular weight polyethylene (UWPE) filler on the shear bond strength between the repaired surface of the rapid heat-cured and the reinforced autopolymerized acrylic resin. Fifty-six circular (15 × 3.3 mm2) rapid heat-cured resins were made and assigned equally to seven different groups. These were later bonded to fifty-six circular-reinforced autopolymerized acrylic resin specimens. Every test group included a control group, along with applying 1% and 2% SEG, 0.5% SEG/UWPE, 1% SEG/UWPE, and 1% and 2% UWPE. The universal testing machine was utilized to conduct the shear bond strength test. The repaired surface of these samples was assessed. Besides, the mode of failure was visualized under stereo microscope. The shear bond strength of all experimental groups was significantly higher than that of the control group. Group 3 with the addition of 1% SEG demonstrated the highest significance (12.86 MPa). The mode of failure for most of specimens was a mixed failure. Thus, it is indicated that enhancing the resin with 1% short E-glass fiber significantly improves the shear bond strength between repaired surface of the rapid heat-cured acrylic resin denture base and the reinforced autopolymerized acrylic resin.